Relapsing Bickerstaff Brainstem Encephalitis After Autologous Stem Cell Transplant. Issue 4 (June 2020) - Malhotra, Ashwin; Latov, Norman
Abstract : Abstract: Bickerstaff brainstem encephalitis, widely considered to be associated with Miller Fisher and Guillain–Barré syndromes, is a rare disease state defined by the triad of ophthalmoplegia, ataxia, and decreased consciousness. The presence of central nervous system involvement, commonly in the form of impaired arousal, solidifies it as a unique entity. We present a case of this rare syndrome after autologous stem cell transplant.